Seasonal Pollinosis: Analysis in Rural and Urban Settings of Surkhandaryo Region - Muhayyo, Xudoyberdiyeva (American Journal of Bioscience and Clinical Integrity, 2025)
Seasonal pollinosis, commonly known as hay fever, is a significant public health issue characterized by allergic reactions to airborne pollen. The unique climate and geographical conditions of Surkhandaryo region provide a rare opportunity to study the spread and impact of seasonal pollinosis. This paper analyzes the differences in the manifestation, distribution, and management of pollinosis in rural and urban areas, taking into account environmental, demographic, and medical factors. The findings aim to inform the development of targeted prevention and treatment strategies for the population of Surkhandaryo region.